IDENTIFIKASI PENGARUH BENTUK DESAIN BANGUNAN TERHADAP INTENSITAS KONSUMSI ENERGI MELALUI METODE SIMULASI KOMPUTASIONAL SEFAIRA - A'yun, Qurrotul (Nature : National Academic Journal of Architecture, 2023)
Currently, architectural items need to be energy efficient in addition to being aesthetically pleasing and practical. Residential or residential-type objects are not exempt. Residential buildings need to be kept at comfortable temperatures and with appropriate lighting while also being mindful of their energy usage. The importance of energy usage in building design depends on several aspects. These include the building's orientation, the material of the building envelope, the shape of the window, and the building plan and room volume. In order to attain the Energy Consumption Intensity (IKE) value required by the 2012 Regulations of the Ministry of Education and Culture and the Ministry of Energy and Mineral Resources, a suitable form of building design is therefore necessary. Performance-Based Design is one method that could be used to address this issue. A design methodology known as "performance-based design" takes into account each architectural element's performance. One piece of performance-based design software is Sefaira. To simulate energy use in a design, one must first enter building element and climate data into Sefaira. According to the research findings, a building design is considered efficient with an IKE if it satisfies the following criteria: (1) the building's geometric shape leads to a curved shape or has many sides; (2) the building's proportions are the same or, if it is slightly elongated, it is oriented towards the west and east; (3) the building reduces the amount of glazing material coverings; and (4) the building uses external Venetian shading.